Knowledge and attitudes about voluntary surgical contraception in patients in the CS Colcabamba Tayacaja Huancavelica - Benites, . (2015)
The aim of this study was to evaluate the knowledge of attitudes in a rural population adopting birth control voluntary surgical contraception in order to improve the coverage of family planning program.